2004
DOI: 10.1073/pnas.0306731101
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-mediated activation of neuronal kainate receptors

Abstract: Exogenous kainate receptor agonists have been shown to modulate inhibitory synaptic transmission in the hippocampus, but the pathways involved in physiological activation of the receptors remain largely unknown. Accumulating evidence indicates that astrocytes can release glutamate in a Ca 2؉ -dependent manner and signal to neighboring neurons. We tested the hypothesis that astrocyte-derived glutamate activates kainate receptors on hippocampal interneurons. We report here that elevation of intracellular Ca 2؉ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 195 publications
(136 citation statements)
references
References 55 publications
6
129
1
Order By: Relevance
“…Hippocampal slices were loaded with the Ca 2+ indicator, fluo-4/AM and viewed by twophoton laser scanning microscopy. The preferential loading of fluorescent acetoxymethyl esters indicators by astrocytes has been extensively reported [20][21][22] . Bath application of 4-AP potently initiated astrocytic Ca 2+ signaling expressed as infrequent Ca 2+ oscillations (Fig.…”
Section: Ttx-insensitive Astrocytic Ca 2+ Signaling In Experimental Smentioning
confidence: 92%
See 3 more Smart Citations
“…Hippocampal slices were loaded with the Ca 2+ indicator, fluo-4/AM and viewed by twophoton laser scanning microscopy. The preferential loading of fluorescent acetoxymethyl esters indicators by astrocytes has been extensively reported [20][21][22] . Bath application of 4-AP potently initiated astrocytic Ca 2+ signaling expressed as infrequent Ca 2+ oscillations (Fig.…”
Section: Ttx-insensitive Astrocytic Ca 2+ Signaling In Experimental Smentioning
confidence: 92%
“…5a) 22 . Increases in astrocytic Ca 2+ evoked by uncaging of NP-EGTA triggered in 8 of 12 experiments a PDS, whereas UV-flash in an identical fashion of slices not loaded with NP-EGTA failed to increase astrocytic Ca 2+ concentration or to evoke PDSs (n = 15) (Fig.…”
Section: Photolysis Of Caged Ca 2+ In Astrocytes Triggers Pdssmentioning
confidence: 99%
See 2 more Smart Citations
“…Some pathways involved in physiological activation of KA receptors are still unknown, 7 although physiological studies have identified both post-and presynaptic roles for KA receptors. This class of receptors has also been suggested to play an important role in short-and long-term synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%